2001
DOI: 10.1007/bf02234823
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of fecal incontinence on quality of life?

Abstract: A Wexner score of 9 or higher indicates a significant impairment of quality of life and can therefore be used in decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
193
2
21

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(226 citation statements)
references
References 13 publications
10
193
2
21
Order By: Relevance
“…Their median (IQR) loss on the 1-h pad test was 12 (4-28) g, indicating that their incontinence tended to be moderate [18]. The median score was 9.5/20 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(7)(8)(9)(10)(11)(12). Of the 207 women, one did not undergo a 1-h pad test, two did not complete a FVC and another could not estimate the frequency of her incontinent episodes because of constant leakage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their median (IQR) loss on the 1-h pad test was 12 (4-28) g, indicating that their incontinence tended to be moderate [18]. The median score was 9.5/20 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(7)(8)(9)(10)(11)(12). Of the 207 women, one did not undergo a 1-h pad test, two did not complete a FVC and another could not estimate the frequency of her incontinent episodes because of constant leakage.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore became aware that a fecal incontinence grading score had been widely used for several years [11,12]. This scoring system comprises a Likert-type scale which measures the severity and frequency of fecal, liquid and flatal incontinence, and the effect of these on lifestyle as perceived by the patient (maximum composite score 20).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that physical, psychologic, and social functioning of patients are affected, and FI results in a poorer perception of overall health. 10,13,14 However, what is not well described is whether the impact or burden of the condition varies by frequency of incontinence or the population sampled.…”
Section: Fecal Incontinence; Epidemiology; Risk Factors; Prevalencementioning
confidence: 99%
“…Essa avaliação permite a comparação da efetividade das propostas terapêu-ticas entre pacientes, grupos e tipos de tratamento. As escalas Continence Grading Scale ou Escala de Classificação da Incontinência e Fecal Incontinence Severity Index (FISI) são as mais utilizadas nos ensaios clínicos [17][18][19] . Outro estudo de caso com paciente portador de IF teve como objetivo demonstrar que o biofeedback constitui um importante meio terapêutico para o tratamento da dissinergia do assoalho pélvico.…”
Section: Avaliação Fisioterapêutica Na Incontinência Fecalunclassified